Novel organic polymer for UV-enhanced substrate conformal imprint lithography - Fader, R.; Schmitt, H.; Rommel, Mathias; Bauer, A. J.; Frey, Lothar; Ji, R.; Hornung, M.; Brehm, M.; Vogler, M. (Microelectronic Engineering, 2012)
In this work, a novel kind of UV curing polymer is introduced as promising resist for UV-enhanced substrate conformal imprint lithography (UV-SCIL). This fully organic polymer is an epoxy based material and can crosslink via UV exposure to form a solid layer. The curing time of 17 s for this epoxy based resist is ten times shorter compared to commonly used resists for UV-SCIL. Imprints with this material are shown in this work as well as results of an HBr dry etch process of silicon, where the material served as etching mask. Using this polymer as resist for UV-SCIL enables shorter process times whereby the fidelity of the structures remains high. In this work, a novel kind of UV curing polymer is introduced as promising resist for UV-enhanced substrate conformal imprint lithography (UV-SCIL). This fully organic polymer is an epoxy based material and can crosslink via UV exposure to form a solid layer. The curing time of 17 s for this epoxy based resist is ten times shorter compared to commonly used resists for UV-SCIL. Imprints with this material are shown in this work as well as results of an HBr dry etch process of silicon, where the material served as etching mask. Using this polymer as resist for UV-SCIL enables shorter process times whereby the fidelity of the structures remains high.
Keywords: PDMS stamp; SCIL; Soft lithography; Substrate conformal imprint lithography; UV curing epoxides